Dynamic cultures, dynamic responses: The impact on corporate cash holdings amid uncertainty - Kim, Sung Suk; Handoko, Liza; Juliana, Rita (International Journal of Management and Sustainability, 2024)
This study investigates the changes in national culture, economic uncertainty, and their joint effects on corporate cash holdings across 58 countries over the period 2004 to 2020. The study also delves into the importance of national culture in amplifying the impact of economic uncertainty in influencing corporate cash holdings. Drawing on three national cultural dimensions, trust-distrust, collectivism-individualism, and duty-joy orientation-based on the European Value Survey (EVS) and World Value Survey (WVS), we employ a panel data model with a fixed effect approach and incorporate the lag of the independent variable to mitigate potential endogeneity issues. Our findings show that transitions in national culture from collectivism to individualism do not significantly decrease corporate cash holdings. Moreover, a cultural shift from distrust to trust does not result in a decrease in corporate cash holdings. Conversely, a move towards a short-term orientation motivates firms to reduce their cash holdings. The interaction between economic uncertainty and collectivism and individualism tends to increase corporate cash holdings. However, there is no difference in the impacts of the three cultural dimensions for financially constrained and unconstrained firms on corporate cash holdings. This study offers significant practical implications, particularly for policymakers in countries where they have strong collectivistic national culture, which may amplify the effects of economic uncertainty.